2018
DOI: 10.1002/cncr.31373
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in disease presentation and survival of patients with hepatocellular carcinoma: A real‐world experience from 1998 to 2015

Abstract: Over the last 18 years, the percentage of cases of nonalcoholic steatohepatitis HCC has increased but not overall survival. It is interesting to note that only 31% of patients with HCC identified via screening/surveillance received any curative treatment. Further research is needed to better understand the barriers to curative care for patients with HCC and the causes of the lack of improvement in survival in the more recent patient cohort. Cancer 2018;124:2588-98. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…[ 21 ] Other studies also found that among HCC patients, Asian patients had higher survival rates although none have been able to discern a cause. [ 22 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Other studies also found that among HCC patients, Asian patients had higher survival rates although none have been able to discern a cause. [ 22 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding from our study was that those of Asian ethnicity were over 70% less likely to die than those of non‐Asian ethnicity, although the country/region of residence was not significant. Although the reasons for this ethnic disparity remain unclear, it is a phenomenon that has long been described in several prior studies of the multiethnic U.S. population . One recent study analyzed 1,284 Asian and 7,072 non‐Hispanic white patients in a Surveillance, Epidemiology, and End Results Medicare‐linked database, 1994‐2011 .…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of hepatocellular carcinoma (HCC) ranks the third among malignant tumors in the world, with about 1 million new cases diagnosed each year, and the incidence rate of HCC continues to rise [1,2]. Due to the late diagnosis, drug resistance, tumor recurrence and metastasis, etc., the 5-year overall survival (OS) rate of HCC is low of approximately 7% [3,4].…”
Section: Introductionmentioning
confidence: 99%